Origin of stereoselectivity and multidimensional quantitative analysis of ligand effects on yttrium-catalysed polymerization of 2-vinylpyridine. Issue 22 (30th September 2019) - Zhao, Yanan; Lu, Han; Luo, Gen; Kang, Xiaohui; Hou, Zhaomin; Luo, Yi
Abstract : Through a combination of density functional theory (DFT) calculations and multivariate regression analysis, the origin of the stereoselectivity of yttrium-catalysed polymerization of 2-vinylpyridine (2VP) has been investigated. Abstract : Through a combination of density functional theory (DFT) calculations and multivariate regression analysis, the origin of the stereoselectivity of yttrium-catalysed polymerization of 2-vinylpyridine (2VP) has been investigated. Having achieved an agreement between theory and experiment, it is found that the stereoselectivity is mainly affected by the steric effects of ancillary ligand 2-methoxyethylamino-bis(phenolate) and varies with the relative steric hindrance of the two ortho -substituents near the metal center, shedding new light on rational design of stereoselective polymerization catalysts.